Post-Military Politics and ‘Emi Lokan’ Democracy in Nigeria - Remi Chukwudi Okeke (Polish Political Science Yearbook, 2025)
This paper interrogated post-military politics and ‘Emi Lokan’ democracy in Nigeria. It is a significant contribution to the ongoing academic focus on consolidating democracy in the country. According to the research hypothesis, post-military politics in the country still contain some unnecessary military-governance propensities that have not been fully identified for invalidation. The study examined the meaning of ‘Emi Lokan’ democracy. It investigated its democratic implications. The work was based on a qualitative research design, embedding the consultation of secondary sources of non-numeric data. A key message of the contribution is that the influence of military culture in the current democratic order in the country has remained undiminished. The work found that the ‘Emi Lokan’ political belief in Nigeria owes its distasteful origin to the interference of the military in the governance affairs of the nation. It is concluded in the paper that the undesirable ‘Emi Lokan’ democracy can only be stopped in the country by the coming together of a manifestly new breed of politicians. An auspicious attempt was made in this regard during the 2023 presidential election in the nation.